CRIMINAL LIABILITY FOR ILLEGAL FUND TRANSFERS: A CASE STUDY OF DECISION NUMBER 811/PID.SUS/2022/PN.JKT.TIM - Muhamad Ashil Firdaus; Ibrahim Danjuma; Rizka Nurliyantika (Sriwijaya Crimen and Legal Studies, 2026)
This study aims to analyse criminal liability for perpetrators of illegal fund transfer under Article 82 of Law Number 3 of 2011 concerning Fund Transfer and to examine the fulfillment of the elements of criminal offenses in Decision Number 811/Pid.Sus/2022/PN.Jkt.Tim. The research adopts a normative juridical approach by examining statutory regulations, legal doctrines, and relevant judicial decisions concerning fund transfer crimes and cyber-enabled financial offenses in Indonesia. In addition, the study reviews secondary legal materials, including legal textbooks, journal articles, and scholarly writings related to criminal law, cybercrime, and electronic financial transactions. The results of the study indicate that Article 82 of Law Number 3 of 2011 serves as a specific legal provision that criminalizes any person who intentionally receives or accommodates funds known or reasonably suspected to originate from unlawfully made fund transfer orders. The existence of this provision reflects the state’s commitment to adapting criminal law to the rapid development of digital financial systems and cyber-financial crimes. The analysis of Decision Number 811/Pid.Sus/2022/PN.Jkt.Tim demonstrates that all criminal elements under Article 82 were legally fulfilled, particularly the elements of “any person,” “intentionally,” “receives or accommodates,” and “funds known or reasonably suspected to originate from unlawful fund transfer orders.” The court found that the defendant knowingly provided and controlled multiple bank accounts used to receive and redistribute funds derived from fraudulent electronic transactions through digital financial platforms. However, the effectiveness of the implementation of Article 82 remains constrained by several factors, including the sophistication of cybercrime methods, difficulties in tracing electronic transactions, the use of intermediary accounts, and the limited capacity of law enforcement authorities in handling digital evidence and cyber-financial investigations. In addition, public awareness regarding the legal consequences of facilitating suspicious financial transactions remains relatively low, thereby increasing the risk of unlawful fund transfer activities within electronic financial systems. On the other hand, the law provides legal protection through criminal sanctions, judicial enforcement mechanisms, and regulations governing electronic financial transactions aimed at maintaining legal certainty and public trust in Indonesia’s digital banking sector. Therefore, stronger coordination between financial institutions, regulators, and law enforcement agencies, accompanied by technological development and public legal education, is necessary to ensure effective law enforcement and protection against illegal digital fund transfer activities in Indonesia.